Implementation of Foot Exercise Activities to Improve the Ankle BrachialIndex (ABI) (JONAH : Journal of Nursing and Homecare, 2025)
Diabetes Mellitus(DM) is a metabolic disorder characterized by elevated blood glucose levels (hyperglycemia). If this condition persists over time, it can lead to serious complications such as neuropathy or nerve damage. The high prevalence of Diabetes Mellitus and the lack of physical activity among patients necessitate simple and affordable activities, such as foot exercises, which can be performed anytime and anywhere without causing complications. To describe the implementation of foot exercise activities to improve the Ankle Brachial Index (ABI) values in patients with Type II Diabetes Mellitus. This study employed a case study design with a descriptive approach involving two subjects diagnosed with Type II Diabetes Mellitus. The research was conducted from March 11 to March 17, 2025. ABI measurements were taken one day before (H-1) and one day after (H+1) the foot exercise intervention, which consisted of four sessions of 30 minute foot exercises. ABI valuesimproved postintervention in both subjects. Subject I's right ABI increased from 0.9425 to 0.96, and left from 0.9626 to 0.98. Subject II's right ABI improved from 0.875 to 0.9025, and left from 0.9275 to 1. : Foot exercise activities improved ABI values in both patients. Foot exercise activities should be done independently by patients with Type II DM to improve circulation and prevent complications.
Keywords: Diabetes Mellitus, ABI values, Foot Exercise,Neuropathy